2022
DOI: 10.3390/antibiotics11111657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fitness Cost, Stability, and Conjugation Frequencies of tet(X4)-Positive Plasmids in Chicken and Pig Escherichia coli

Abstract: The large-scale epidemic of the tet(X4) gene in the livestock and poultry industry is threatening public health; however, there is still a lack of comparative studies on tet(X4)-bearing plasmids in chicken and pig Escherichia coli. To evaluate the prevalence trend of tet(X4)-bearing plasmids and the factors influencing their persistence in the livestock and poultry industry, we examined the fitness cost, stability under tetracyclines pressure, and conjugation frequencies at various temperatures of six tet(X4)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The results showed that the conjugational frequency of the tet (X4)-positive plasmids ranged from 10 −6 to 10 −4 , and the optimal conjugational temperature was different for tet (X4)-positive plasmids tested. Liu et al (2022b ) found that IncFII-type tet (X4)-positive plasmids had a higher conjugational frequency at 37°C, while IncX1-type tet (X4)-positive plasmids had a higher conjugational frequency at 42°C. This suggests that IncFII-type tet (X4)-positive plasmids were more likely to spread in porcine E. coli , while IncX1-type tet (X4)-positive plasmids are more likely to spread in chicken E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the conjugational frequency of the tet (X4)-positive plasmids ranged from 10 −6 to 10 −4 , and the optimal conjugational temperature was different for tet (X4)-positive plasmids tested. Liu et al (2022b ) found that IncFII-type tet (X4)-positive plasmids had a higher conjugational frequency at 37°C, while IncX1-type tet (X4)-positive plasmids had a higher conjugational frequency at 42°C. This suggests that IncFII-type tet (X4)-positive plasmids were more likely to spread in porcine E. coli , while IncX1-type tet (X4)-positive plasmids are more likely to spread in chicken E. coli .…”
Section: Discussionmentioning
confidence: 99%